2023
DOI: 10.3390/ma16031097
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Performance Optimization of Grouting Backfill Material Based on Mechanically Ground Coal Gangue Utilizing Urea and Quicklime

Abstract: Previously conducted studies have established that grouting backfill in mining-induced overburden bed separation and mined-out areas with broken rocks provides an efficient strategy to control strata movement and surface subsidence caused by underground mining. Grouting backfill materials (GBMs) based on coal gangue (CG) are highly desirable in coal mining for accessibility to abundant CG and urgent demand for CG disposal. However, CG is generally employed as coarse aggregate due to rather rigid and inert prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
1
0
Order By: Relevance
“…According to the reference [44], the reinforced impermeable material needs a certain shear strength to prevent the slurry stone body from being squeezed out of the fissure by water pressure, so as to resist the seepage failure of high water pressure. This performance can be checked with the Buckingham-Reiner formula:…”
Section: Water Plugging Performance Analysis Of Grouting Materialsmentioning
confidence: 99%
“…According to the reference [44], the reinforced impermeable material needs a certain shear strength to prevent the slurry stone body from being squeezed out of the fissure by water pressure, so as to resist the seepage failure of high water pressure. This performance can be checked with the Buckingham-Reiner formula:…”
Section: Water Plugging Performance Analysis Of Grouting Materialsmentioning
confidence: 99%
“…For example, the material is conveniently inserted to gap via piping, effectively occupying goaf cavity as well as significantly mitigating the potential for surface subsidence resulting from goaf collapse (Xu et al, 2020;Shrestha et al, 2022). Wang et al proposed a new method of using coal gangue powder as the dominant component in grouting backfill materials for underground mining with optimized slurry transportability and compressive strength using urea and quicklime as additives (Wang et al, 2023). Yuan et al used molecular dynamics simulations for relationship between crosslinking degree as well as properties for polyurethane grouting materials, providing insights into their microstructure and thermomechanical properties (Yuan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [10] replaced cement with a part of gangue ground to fine ash to prepare concrete, and the results showed that when the replacement rate was approximately 15%, the properties of the concrete were almost the same as those of pure cement concrete. Chen et al [11] reviewed the current research progress of domestic and foreign scholars on the mechanical properties and durability of gangue, pumice, and ceramic light aggregate concrete, obtained different types of hard bone materials, particle size, shape, and substitution rate and introduced the effects of the mixture and aggregate activation on the mechanical properties and durability of concrete [12][13][14]. However, the preparation of dry-mixed mortar from coal gangue and its application have not been reported.…”
Section: Introductionmentioning
confidence: 99%